Distinct actin oligomers modulate differently the activity of actin nucleators. (11th August 2015) - Qu, Zheng; Silvan, Unai; Jockusch, Brigitte M.; Aebi, Ueli; Schoenenberger, Cora‐Ann; Mannherz, Hans Georg
<x xml:space="preserve">Abstract</x> Polymerization of actin monomers into filaments requires the initial formation of nuclei composed of a few actin subunits; however, their instability has hindered their detailed study. Therefore we used chemically crosslinked actin oligomers to analyse their effect on actin polymerization. Actin dimer (upper dimer, UD), trimer and tetramer intermolecularly crosslinked by phenylene‐bismaleimide along the genetic helix (between Lys199 and Cys374) were isolated by gel filtration and found to increasingly stimulate actin polymerization as shown by the pyrene assay and total internal reflection fluorescence microscopy. In contrast, the so‐called lower actin dimer (LD) characterized by a Cys374‐Cys374 crosslink stimulated actin polymerization only at low but inhibited it at high concentrations. UD and trimer stimulated the repolymerization of actin from complexes with thymosin β4 (Tβ4) or profilin, whereas the LD stimulated repolymerization only from the profilin : actin but not the actin : Tβ4 complex. In vivo, actin polymerization is stimulated by nucleation factors. Therefore the interaction and effects of purified LD, UD and trimer on the actin‐nucleating activity of gelsolin, mouse diaphanous related (mDia) formin and the actin‐related protein 2/3 (Arp2/3) complex were analysed. Native gel electrophoresis demonstrated binding of LD, UD and trimer to gelsolin and its fragment G1–3, to the FH2 domains of the formins mDia1 and mDia3, and to Arp2/3 complex. UD and trimer increased the nucleating activity of gelsolin and G1–3, but not of the mDia‐FH2 domain nor of the Arp2/3 complex. In contrast, LD at equimolar concentration to Arp2/3 complex stimulated its nucleating activity, but inhibited that of mDia‐FH2 domains, gelsolin and G1–3, demonstrating differential regulation of their nucleating activity by dimers containing differently oriented actin subunits.